Purkinje Cell Activity in the Medial and Lateral Cerebellum During Suppression of Voluntary Eye Movements in Rhesus Macaques - Avila, Eric; Flierman, Nico A.; Holland, Peter J.; Roelfsema, Pieter R.; Frens, Maarten A.; Badura, Aleksandra; De Zeeuw, Chris I. (Frontiers in Cellular Neuroscience, 2022)
Volitional suppression of responses to distracting external stimuli enables us to achieve our goals. This volitional inhibition of a specific behavior is supposed to be mainly mediated by the cerebral cortex. However, recent evidence supports the involvement of the cerebellum in this process. It is currently not known whether different parts of the cerebellar cortex play differential or synergistic roles in the planning and execution of this behavior. Here, we measured Purkinje cell (PC) responses in the medial and lateral cerebellum in two rhesus macaques during pro- and anti-saccade tasks. During an antisaccade trial, non-human primates (NHPs) were instructed to make a saccadic eye movement away from a target, rather than toward it, as in prosaccade trials. Our data show that the cerebellum plays an important role not only during the execution of the saccades but also during the volitional inhibition of eye movements toward the target. Simple spike (SS) modulation during the instruction and execution periods of pro- and anti-saccades was prominent in PCs of both the medial and lateral cerebellum. However, only the SS activity in the lateral cerebellar cortex contained information about stimulus identity and showed a strong reciprocal interaction with complex spikes (CSs). Moreover, the SS activity of different PC groups modulated bidirectionally in both of regions, but the PCs that showed facilitating and suppressive activity were predominantly associated with instruction and execution, respectively. These findings show that different cerebellar regions and PC groups contribute to goal-directed behavior and volitional inhibition, but with different propensities, highlighting the rich repertoire of the cerebellar control in executive functions.